2001
DOI: 10.1091/mbc.12.11.3618
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Necrosis Factor-α Induces Stress Fiber Formation through Ceramide Production: Role of Sphingosine Kinase

Abstract: Tumor necrosis factor-α (TNF-α) is a proinflammatory cytokine that activates several signaling cascades. We determined the extent to which ceramide is a second messenger for TNF-α-induced signaling leading to cytoskeletal rearrangement in Rat2 fibroblasts. TNF-α, sphingomyelinase, or C2-ceramide induced tyrosine phosphorylation of focal adhesion kinase (FAK) and paxillin, and stress fiber formation. Ly 294002, a phosphatidylinositol 3-kinase (PI 3-K) inhibitor, or expression of dominant/negative Ras (N17) comp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
52
0
1

Year Published

2002
2002
2018
2018

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 70 publications
5
52
0
1
Order By: Relevance
“…Several studies suggest that sphingomyelinases and ceramidases are activated in response to the same inducers that stimulate SK (11,(25)(26)(27)(28)(29), thus raising the possibility that sphingosine could be generated in or close to the plasma membrane concomitant with SK activation. These studies are consistent with S1P being generated in a location conducive for swift secretion out of the cell.…”
Section: Table I Effects Of Pkc Modulators On Sk Translocation In Hekmentioning
confidence: 99%
“…Several studies suggest that sphingomyelinases and ceramidases are activated in response to the same inducers that stimulate SK (11,(25)(26)(27)(28)(29), thus raising the possibility that sphingosine could be generated in or close to the plasma membrane concomitant with SK activation. These studies are consistent with S1P being generated in a location conducive for swift secretion out of the cell.…”
Section: Table I Effects Of Pkc Modulators On Sk Translocation In Hekmentioning
confidence: 99%
“…36,50,51 Our work with Rat2 fibroblasts demonstrated that TNFa, sphingomyelinase and C 2 -ceramide increase Ras-GTP concentrations, the binding of Ras to activated PI 3-K 23 cause the subsequent activation Rac, Cdc42 and the physical interaction of Cdc42 with activated PAK. 24 The involvement of PI 3-K, pp70 S6K and ERK in increasing GLUT1 concentrations is confirmed by the partial inhibition of the ceramide effect by Ly 294002, rapamycin and PD 98059, which inhibit PI 3-K activity and the activations of pp70 S6K and ERK, respectively. Ly294002 could also have inhibited the mammalian target of rapamycin (mTOR).…”
Section: Discussionmentioning
confidence: 91%
“…23 Therefore, the effects of short-chain ceramides are mainly direct rather than involving metabolism to sphingosine or sphingosine 1-phosphate. 23,24 TNFa and ceramides stimulate PI 3-K in 3T3 L1 adipocytes, 22,25 fibroblasts, 23,24 smooth muscle cells, 26 osteoclasts 45 and macrophages. 46 These increases in PI 3-K are associated with protection from apoptosis and increased division rather than cell death.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations